2018
DOI: 10.1037/pag0000231
|View full text |Cite
|
Sign up to set email alerts
|

Aging and attention to self-selected emotional content: A novel application of mobile eye tracking to the study of emotion regulation in adulthood and old age.

Abstract: Previous studies of attentional deployment to a single stream of experimenter-selected affective stimuli have found that compared to younger adults, older adults attend relatively more to positive and less to negative stimuli, and this can relate to better mood for them. Past studies of situation selection have yielded a contrasting picture of age similarity. In everyday life, attentional deployment is fundamentally and dynamically related to situation selection, but prior studies have investigated them only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…This association is in keeping with results in young people from the general population with depression (Joormann & Stanton, 2016). However, few studies in later life have examined the cognitive domain of self-regulation of emotion (most have focused on the agerelated positivity effect -the finding that older people tend to be more attentive to positive compared to negative stimuli -using experimental methods, see Isaacowitz et al, 2018;Mather, 2012). While LLD is strongly associated with executive function difficulties, most studies have Cardiovascular health in autistic adults 12 focused on aspects of executive function such as inhibitory control or working memory (Alexopoulos et al, 2005;Barch et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…This association is in keeping with results in young people from the general population with depression (Joormann & Stanton, 2016). However, few studies in later life have examined the cognitive domain of self-regulation of emotion (most have focused on the agerelated positivity effect -the finding that older people tend to be more attentive to positive compared to negative stimuli -using experimental methods, see Isaacowitz et al, 2018;Mather, 2012). While LLD is strongly associated with executive function difficulties, most studies have Cardiovascular health in autistic adults 12 focused on aspects of executive function such as inhibitory control or working memory (Alexopoulos et al, 2005;Barch et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…As mentioned before, the exposure time may be a key factor for the attentional bias of faces. Negative attentional bias appears in a relatively earlier time (Wright et al, 2006) and positive attentional bias appears relatively late (Isaacowitz et al, 2018). In this study, the exposure time of the facial image is 1,000 ms, which is relatively long, and we found a positive attentional bias in mature adults.…”
Section: Discussionsupporting
confidence: 43%
“…For example, when participants are given choices of how to appraise videos, they may be less likely to use response modulation. Some research has shown that when given the option to use situation selection, people are less likely to use attentional deployment (Isaacowitz, Livingstone, Richard, & Seif El-Nasr, 2018).…”
Section: Discussionmentioning
confidence: 99%